Event Studies In Management Research: Theoretical And Empirical Issues - McWilliams, Abagail; Siegel, Donald S. (Academy of Management Journal, 1997)
We examined the use of event studies in management research and found that there was inadequate attention paid to theoretical and research design issues. This lack of attention may lead to false inferences regarding the significance of the events and the validity of the theories being tested. To illustrate the extent of this problem, we attempted to replicate three recent studies. To guide authors and reviewers, we out-line procedures for appropriate use of the event study method.